Europarties in the system of representative democracy of the European Union – in search of identity - Čupić, Zoran (Sociološki pregled, 2022)
The Lisbon Treaty stipulates that the functioning of the European Union will be based on representative democracy. The main bearers of representative democracy should be political parties, in this case European political parties. Therefore, the subject of this paper is the position of European parties in the political system of the European Union. The basic question is whether the Europarties are able to contribute to the democratic functioning of the political system of the European Union and thus build their recognizable identity. If we take into account the existing constitutional order of the European Union and the place of political parties in it, it is obvious that they are not able to contribute to forming European political awareness and to expressing the political will of the Union citizens.